2021
DOI: 10.3390/jcm10091816
|View full text |Cite
|
Sign up to set email alerts
|

Screening for TB in Hospitalised Patients with Inflammatory Bowel Disease before Anti-TNF Therapy: Is QuantiFERON® Gold Testing Useful?

Abstract: Background—Tumour necrosis factor alpha (TNFα) plays an important role in the pathogenesis of inflammatory bowel disease (IBD) and in immunity to Mycobacterium tuberculosis. Patients should be tested for latent tuberculosis infection using interferon-gamma release assays (IGRA/QF) prior to anti-TNFα therapy. Indeterminate QF results can delay anti-TNFα therapy. We sought to investigate factors associated with indeterminate QF results. Method—Retrospective study of all IGRA tests requested for gastroenterology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…9 TNF-α plays an important role in the recruitment and activation of immune cells that control viral and Mycobacterium tuberculosis infection; thus, blockade of TNF-α might exacerbate infections. 13,18 According to a previous report, an infant died because of disseminated BCG infection after BCG at 3 months of age. 10 He was exposed to IFX in utero because his mother had received IFX therapy every 8 weeks at a dose of 10 mg/kg for Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 TNF-α plays an important role in the recruitment and activation of immune cells that control viral and Mycobacterium tuberculosis infection; thus, blockade of TNF-α might exacerbate infections. 13,18 According to a previous report, an infant died because of disseminated BCG infection after BCG at 3 months of age. 10 He was exposed to IFX in utero because his mother had received IFX therapy every 8 weeks at a dose of 10 mg/kg for Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Similarly, a recent meta-analysis showed that the TB incidence following anti-TNF therapy was only dependent on local TB burden, and was independent of disease and anti-TNF type. 5 Hence, the title of our paper does state explicitly that this strategy is for the setting of TB endemic regions.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…This is evident in the studies from India which have shown rates of TB reactivation as high as 11.6% following anti‐TNF therapy in patients with inflammatory bowel diseases which is in direct contrast to the British audit, which did not find any case of reactivation in 360 patients 3,4 . Similarly, a recent meta‐analysis showed that the TB incidence following anti‐TNF therapy was only dependent on local TB burden, and was independent of disease and anti‐TNF type 5 . Hence, the title of our paper does state explicitly that this strategy is for the setting of TB endemic regions.…”
mentioning
confidence: 95%
“…Kumar et al find that 33% of the latent TB cases were found by CT only 3 . In a recent British audit, no cases of reactivation of latent TB were found in 360 patients 4 . India currently accounts for the highest number of new TB cases in the world, with an incidence of 193 per 100,000 population in contrast to the UK incidence of eight per 100,000 5,6 .…”
mentioning
confidence: 99%
“…However, IGRA testing does have its own problems. IGRA testing in patients exposed to steroids or in‐patients with acute IBD flares more often produces indeterminate results, 4 leading to additional tests and consequent delays in therapy.…”
mentioning
confidence: 99%